Qur’an Memorization as a Pillar of Character Building for Madrasah Ibtidaiyah Students in Progressive Islam - Choirun Nisa; Eka Danik Prahastiwi; Minsih; Nadia Kumalasari; Siti Norlina Muhammad (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2025)
Objectives:  This study aims to optimize the Tahfizhul Qur’an program to strengthen students’ religious character based on Progressive Islam at MIM Adab Baleharjo, Pacitan, Indonesia. Method: A qualitative descriptive approach was used to examine character education through Quran memorization at MIM Adab Baleharjo, Pacitan. Purposively selected informants included students, tahfizh teachers, parents, and principals. Data were collected through observation, interviews, and document analysis, and analyzed using data reduction, presentation, and conclusion drawing, with triangulation ensuring credibility and validity. Results: The study shows that the Tahfidzul Qur’an program strengthens students’ character particularly discipline, honesty, responsibility, empathy, and love for the Qur’an while reflecting Progressive Islam values such as renewal (tajdid), rationality, social justice, moderation, inclusivity, and educational technology Theoretical Contribution: Theoretically, this research enhances Islamic character education by strengthening a holistic approach that integrates Qur’an memorization with Progressive Islamic values, in line with Thomas Lickona’s framework and Al-Ghazali’s moral education concept. Implication: The Qur’an memorization program can be an alternative to build character and instill progressive Islamic values. This study is limited to a single site and a qualitative design, reducing its generalizability. Future research should use mixed methods and examine the various influences of memorizing the Qur’an